Risk Attitudes and Conservation Decisions: A Case Study of Family Forest Owners in Georgia. Issue 2 (26th October 2018) - Kang, Moon Jeong; Siry, Jacek P; Colson, Gregory; Ferreira, Susana
Abstract: We examine the role of individual risk attitudes in family forest owners' decisions regarding participation in payments for ecosystem services (PES) programs. We elicited participants' risk attitudes using the multiple price list methodology and obtained their preferences toward hypothetical PES program designs using a choice experiment contained in a survey instrument. Forest owners required more compensation as the contract length increased and preferred cash payments over tax credits, regardless of their risk attitudes. They also required higher payments for wider stream buffers and for limiting increases in pine plantation area on enrolled parcels. Risk-averse forest owners were more likely to participate in the hypothetical PES programs than risk-neutral and risk-seeking forest owners. Furthermore, risk-averse forest owners required less compensation than risk-tolerant forest owners. Research findings suggest that identifying and targeting risk-averse forest owners in the process of designing and advertising PES programs could increase conservation success with lower budgets.